The Party's Over: Sex, Gender, and Orientalism in the Koreagate Scandal of the 1970s. - SANG-HEE LEE, SHELLEY (Frontiers: A Journal of Women Studies, 2018)
The article presents an essay which builds on intersectional scholarship about gender, sexuality, and orientalism during the Cold War as well as Asian American history in the post-1965 era. It mentions that the essay examines how through media coverage of Koreagate, and in particular of Suzi Park Thomson and Tongsun Park, we can trace the shift ing grounds of race, gender, and sexuality during the 1970s.